الصعوبات النفس حركية و آثارها على تعلم الكتابة لدى أطفال الرياض لولاية تقرت - بلابل, زغابي, نور الهدى سناء (University of El-oued, 2022)
تسعى الدراسة إلى التعرف على مدى تأثير الصعوبات النفسية الحركية التي تواجه أطفال الروضة أثناء تعلم الكتابة. أُعتُمد المنهج الوصفي مع الإجراء التحليلي بالإضافة إلى المنهج الإحصائي باعتباره يتماشى مع الموضوع المدروس، وقد أجريت الدراسة على عينة من أطفال الرياض بمدينة تقرت،مستخدمين أداة الاستبانة؛ حيث وزعت على معلمي أطفال الرياض،والّتي بلغت عشرين مربية مع غياب كلي لفئة الذكور، وقد توصلت الدراسة لنتائج نذكر منها:توفير الوقت الملائم لأداء النشاط على أكمل وجه، تدريب الطفل على الطريقة الصحيحة لمسك القلم، تدريب الطفل على وضعية الجلوس المناسبة للكتابة، المراقبة المستمرة للأطفال أثناء الكتابة من قبل المعلم.ولعلاج هذه الصعوبات يجب إتباع مجموعة من الضوابط كاستخدام الأدوات المناسبة للكتابة، تكليف الطفل بتدريبات منزلية في نشاط الخط. The studyseeks to identify the impact of psychomotordifficultiesfaced by kindergartenchildrenwhilelearning to write. The descriptive approachwasadoptedwith the analyticalprocedure in addition to the statisticalmethod as itis in line with the studiedsubject. The studywasconducted on a sample of children in Riyadh in the city of Touggourt, using the questionnaire tool; Whereitwasdistributed to teachers of Riyadhchildren, whichamounted to twentyeducators, with a total absence of the male category, and the studyreachedresults, including:Providing the appropriate time to perform the activity to the fullest, training the child on the correct way to hold the pen, training the child on the appropriatesitting position for writing, and continuous monitoring of childrenwhilewriting by the teacher. To remedythesedifficulties, a set of controls must befollowed, such as usingappropriatewritingtools, assigning the child home exercises in calligraphyactivity.
دراسة نفسية لسانية
Keywords: الكتابة. التعلم. النفس